Post-traumatic changes in energy expenditure and body composition in patients with acute spinal cord injury - Peter Felleiter; Joerg Krebs; Yvonne Haeberli; Wilma Schmid; Stefanie Tesini; Claudio Perret (Medical Journals Sweden, 2017)
Study design: Prospective cohort study. Objective: To investigate the changes in resting energy expenditure and body composition over time in a cohort of patients with spinal cord injury during acute treatment, rehabilitation, and 2 years after the end of rehabilitation. Methods: Adult patients admitted for acute treatment and rehabilitation after traumatic spinal cord injury were recruited. Measurements of resting energy expenditure and body composition were scheduled at 2, 6, 10 and 14 weeks after spinal cord injury, at the end of rehabilitation, and 2 years later. Results: Patients' mean age was 38.8 years (standard deviation 14.0). Resting energy expenditure began to decrease up to the 10-week measurement (p = 0.02) and further decreased after the 130-week measurement (p < 0.001). Body weight was already decreased after the 6-week measurement (p < 0.01) and increased after the end of rehabilitation (p = 0.009). Percentage body fat mass showed similar changes. Conclusion: After an initial decrease in resting energy expenditure, body weight and percentage of body fat, these values levelled off during the rehabilitation period. After the end of the rehabilitation period, body weight and body fat mass increased again to the baseline levels, whereas resting energy expenditure decreased further. These results suggest that rehabilitation programmes should focus on adapting to these foreseeable changes.